None INVESTIGATION INTO DEVICES USED TO CURB CAR HIJACKING IN MAMELODI TOWNSHIP. GAUTENG PROVINCE: None - Adewale Olutola; OSCAR MALULEKA; Jerry Malange (CV. RADJA PUBLIKA, 2025)
Carjacking, also referred to as car hijacking, is a type of robbery where a vehicle is taken from the driver through the use of force, often with the involvement of firearm. South Africa has one of the highest car hijacking rates in the world, with an average of 46 vehicles hijacked daily, or 2 every hour. Technology devices were created to help law enforcement officers to prevent and effectively investigate vehicle hijacking crimes. The purpose of the study was to identify technological devices and other strategies that police can utilize to deter and resolve cases of vehicle hijacking in Mamelodi Township. Additionally, the study aimed to identify all stakeholders from both private and public sectors that can collaborate with the police to prevent the enigma of car hijacking. The study also uncovered all the effects that vehicle hijacking has on the victims of the crime. A qualitative research methodology was adopted for this paper. The study adopted the social learning theory which explains that criminal behaviour is learned just like other criminal behaviour, car hijacking crime is also learned in society. Data collection was done through purposive sampling as it allowed the researcher to choose participants who were well-informed on the topic being explored. Data was collected by using one-on-one or face-to-face semi-structured interviews. Based on the findings. The recommendations of the study include the introduction of new technology devices, adoption of crime prevention strategies from other countries by the police, priority on collaboration between the South African police service and private sectors, installation of devices by vehicle owners to prevent vehicle hijackings, and provision of quality service by the police.